Affirmative action, shifting competition, and human capital accumulation: A comparative static analysis of investment contests - Christopher Cotton; Brent R. Hickman; Joseph Price (Queen's University, Department of Economics, 2020)
We develop a model in which many heterogeneous agents invest in human capital as they compete for better college admission slots or employment opportunities. The model provides theoretical predictions about how affirmative action or preferential treatment policies change the distribution of effort, human capital accumulation, and job/college slot allocations across different population groups. Our findings deliver two key insights. First, incentives to invest in human capital depends substantially on the strength of one's competition. Second, we find evidence of a counter-intuitive role for preferential treatment in promoting overall human capital development.
Keywords: J15; J24; C93; D82; D44; 330; Large Contest; All-Pay Auction; Affirmative Action; College Admissions; Field Experiment; Human Capital